Transcription, mRNA Export, and Immune Evasion Shape the Codon Usage of Viruses - Mordstein, Christine; Cano, Laura; Morales, Atahualpa Castillo; Young, Bethan; Ho, Alexander T; Rice, Alan M; Liss, Michael; Hurst, Laurence D; Kudla, Grzegorz (Genome biology and evolution, 2021)
Abstract The nucleotide composition, dinucleotide composition, and codon usage of many viruses differ from their hosts. These differences arise because viruses are subject to unique mutation and selection pressures that do not apply to host genomes; however, the molecular mechanisms that underlie these evolutionary forces are unclear. Here, we analyzed the patterns of codon usage in 1,520 vertebrate-infecting viruses, focusing on parameters known to be under selection and associated with gene regulation. We find that GC content, dinucleotide content, and splicing and m6A modification-related sequence motifs are associated with the type of genetic material (DNA or RNA), strandedness, and replication compartment of viruses. In an experimental follow-up, we find that the effects of GC content on gene expression depend on whether the genetic material is delivered to the cell as DNA or mRNA, whether it is transcribed by endogenous or exogenous RNA polymerase, and whether transcription takes place in the nucleus or cytoplasm. Our results suggest that viral codon usage cannot be explained by a simple adaptation to the codon usage of the host—instead, it reflects the combination of multiple selective and mutational pressures, including the need for efficient transcription, export, and immune evasion.